Systematic Literature Review: Intergenerational Conflict in Generation Z’s Delayed Marriage Due to Financial Unpreparedness and Parental Expectations Regarding Large, Traditional Weddings Based on Custom and Social Status in Indonesia - Triana Bilqis (CV. Publikasi Indonesia, 2026)
Generation Z in Indonesia tends to postpone weddings due to financial unpreparedness, while parents often have high expectations for holding large weddings according to customs and to maintain the social status of the family. This research aims to conduct a systematic literature review (SLR) on intergenerational conflicts arising from these differences in values and their psychological impact. Using the PRISMA 2020 method, articles were collected from Google Scholar, Sinta, Garuda, and higher education repositories for the 2018-2025 period. A synthesis of 25-40 articles shows that the mismatch between Gen Z's financial readiness with customary demands, dowry or money, and the social prestige of parents causes stress, anxiety, feelings of guilt, marriage phobia, and family relationship tensions. Moderator factors such as urban-rural culture, gender, and the influence of social media reinforce this conflict. This study concludes the importance of psychology-based family counseling interventions and premarital financial literacy involving both generations. Practical implications and recommendations for further research are also discussed.